PENGARUH METODE BERCERITA DALAM MENGEMBANGKAN SIKAP TANGGUNG JAWAB PADA ANAK KELOMPOK A DI TK KARUNIA KEBRAON SURABAYA: THE EFFECT OF STORY METHOD TO DEVELOPING RESPONSIBILITY CHILDREN AT GROUP A KARUNIA KEBRAON KINDERGARTEN SURABAYA - Isabella Hasiana (incrementapedia, 2023)
This research is motivated by the attitude of responsibility in children who are still low. The low level of responsibility in group A children at TK Karunia Kebraon Surabaya is caused by teachers who still often indulge children in completing their assigments,, as well as lack of affirmation in addressing children's behavior. The purpose to be achieved in this research is to find out the influence of storytelling methods in developing attitudes of responsibility in group A children at TK Karunia Kebraon Surabaya. This research uses quantitative research approach with pre-experimental research type using one group pretest-posttest design. The subject of this study was a group A child at TK Karunia Kebraon Surabaya with 15 children. Data collection method used is observation using assessment tools in the form of observation sheets and documentation. Using statistical analysis method with the formulation used is Ttest which is in accordance with the title of the research, namely The Influence of Storytelling Method in Developing Attitudes of Responsibility in Group A Children at Tk Karunia Kebraon Surabaya. Used pre-test and post-test one group design calculated using the formula Ttest. Based on the calculation result using the T test formula that obtained thitung result is 20.25 where the value is greater than the Tttabel value for the significance of 0.05 is 1. It can be concluded that there is an influence of storytelling methods in developing attitudes of responsibility in group A children at TK Karunia Kebraon Surabaya.